2008
DOI: 10.1073/pnas.0804573105
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic rheology and directional mechanotransduction in vascular endothelial cells

Abstract: Adherent cells remodel their cytoskeleton, including its directionality, in response to directional mechanical stimuli with consequent redistribution of intracellular forces and modulation of cell function. We analyzed the temporal and spatial changes in magnitude and directionality of the cytoplasmic creep compliance (⌫) in confluent cultures of bovine aortic endothelial cells subjected to continuous laminar flow shear stresses. We extended particle tracking microrheology to determine at each point in the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 33 publications
6
64
0
Order By: Relevance
“…C, In vivo post-thrombectomy EC counts display heterogeneity across devices predicted by in vitro studies. The number of section samples quantified for 5Max, Trevo, Solitaire, and Separator 3D are n=8,21,20,and 24, respectively. of these devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C, In vivo post-thrombectomy EC counts display heterogeneity across devices predicted by in vitro studies. The number of section samples quantified for 5Max, Trevo, Solitaire, and Separator 3D are n=8,21,20,and 24, respectively. of these devices.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that physiological blood flow and resultant shear stress are crucial for EC maintenance and remodeling after injury [13][14][15][16][17][18][19][20][21][22] and that locally disrupted blood flow contributes to inflammatory cascades. 23 Many of the proposed mechanisms of reperfusion injury after acute ischemic stroke also originate at the EC level.…”
mentioning
confidence: 99%
“…Using this approach, we have shown that axonal stretching occurs during axonal elongation in vivo (Roossien et al, 2013), in cultured neurons from various species (Miller and Sheetz, 2006;O'Toole et al, 2008;Lamoureux et al, 2010a;Lamoureux et al, 2010b;Roossien et al, 2013) and in response to forces generated in or applied to the growth cone (O'Toole et al, 2008;Lamoureux et al, 2010a). Furthermore, in the field of nonneuronal cell biophysics, docked mitochondria are well-accepted fiducial markers for bulk subcellular deformation (Wang et al, 2001;Knight et al, 2006;Gilchrist et al, 2007;Wang et al, 2007;del Alamo et al, 2008;Bell et al, 2012;Silberberg and Pelling, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropic orientation of stress fibers, together with the dynamic FAs, has been linked to the spatial organization of intracellular forces and changes in cell morphology, leading to the reinforcement of cell tension (Lee et al, 2013;Zemel et al, 2010a;Zemel et al, 2010b). The structural and mechanical polarization of the cytoskeleton has been observed in cells responding to diverse types of active mechanical stimuli (del Alamo et al, 2008;Hur et al, 2012;Kaunas et al, 2005). It is thus conceivable that the recruitment of NMIIB, through the DH domain of GEF-H1, to FAs contributes to a polarized distribution of stress fibers and FA formation, thereby generating an increase in intracellular tension and modulating cell shape.…”
Section: Discussionmentioning
confidence: 99%